1996
DOI: 10.1210/endo.137.10.8828505
|View full text |Cite
|
Sign up to set email alerts
|

Histidine decarboxylase expression and histamine metabolism in gastric oxyntic mucosa during hypergastrinemia and carcinoid tumor formation.

Abstract: Histamine is an important stimulator of gastric acid secretion. In experimental animals, inhibition of acid secretion by long term histamine2 receptor blockade causes hypergastrinemia, proliferation of enterochromaffin-like (ECL) cells, and formation of histamine-producing gastric carcinoids. The aim of this study was to examine the role of gastrin in histamine synthesis and metabolism of the oxyntic mucosa of normal, hyperplastic, and carcinoid-bearing Mastomys natalensis. Administration of exogenous gastrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Small intestinal mucosa were obtained after the animals were euthanized, washed in PBS, and immersed in 4% formaldehyde overnight (28). Fixed tissue was mounted edge-on in paraffin blocks.…”
Section: Mastomys Tissue Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Small intestinal mucosa were obtained after the animals were euthanized, washed in PBS, and immersed in 4% formaldehyde overnight (28). Fixed tissue was mounted edge-on in paraffin blocks.…”
Section: Mastomys Tissue Specimensmentioning
confidence: 99%
“…With the use of elutriation and Nycodenz gradient centrifugation of everted normal and carcinoid-containing stomachs, 85-95% pure preparation of gastric EC-like (ECL) cells can be obtained (26,31). Studies of purified gastric ECL cells have demonstrated the key regulatory role of the histamine enzyme histidine decarboxylase in gastric ECL cell histamine secretion, identified the presence of gastrin CCK 2 and PACAP receptors and defined their key roles in proliferation and secretion (28,31,32,50), and delineated the presence of SST receptor 2 (SST R 2) and the inhibitory role of octreotide in both secretion and proliferation (4,45). With the use of a somewhat similar approach, preparations of neurotensin and enteroglucagon cells have been obtained from the canine ileum (2,6).…”
mentioning
confidence: 99%
“…It is the only enzyme that forms histamine in mammals. Histamine is well known to act as an important physiological modulator (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). HDCs have been purified from the soluble fraction of various tissues and found to be a dimer consisting of two identical 53-kDa subunits (13)(14)(15)(16), while the size of cDNA-deduced HDC is around 74 kDa (17)(18)(19).…”
mentioning
confidence: 99%
“…The broad range of excretion values (0.9 to 30 mmol/mol creatinine), from normal up to a high level as found here in two patients with systemic mastocytosis, indicate that the method can be satisfactorily applied for evaluation of histamine turnover under various clinical conditions. Moreover, the method has also been successfully used for t-MeImAA analysis in some laboratory animals, as reported for mastomys [22] and rat [23]. The HPLC chromatograms obtained from these animal urines looked very similar to human ones, and interestingly the excretion of t-MeImAA was of the same order of magnitude as in man when corrected for the creatinine excretion.…”
Section: Discussionmentioning
confidence: 59%